2021
DOI: 10.3904/kjim.2019.355
|View full text |Cite
|
Sign up to set email alerts
|

Fasting glucose level and all-cause or cause-specific mortality in Korean adults: a nationwide cohort study

Abstract: Background/Aims: Although people with diabetes have been shown to have higher mortality than people without diabetes, there is a lack of data on the association between fasting glucose (FG) levels and cause-specific mortality rates in the general population. Methods: A total of 326,547 Korean adults over 20 years of age, who had received a health checkup between 2006 and 2008 were selected from the Korean National Health Insurance Service sample cohort dataset and followed until 2015. We estimated hazard ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In summary, we found that patients with YOD presented different phenotypes at diagnosis compared with those with late-onset T2DM. In particular, they tend to be more obese and have worse glycemic profiles, which is predicted to make the disease worse in the future, considering that the FPG level and BMI are important predictors of morbidity and mortality [ 47 ].…”
Section: Yod Among People With New-onset T2dm In South Koreamentioning
confidence: 99%
“…In summary, we found that patients with YOD presented different phenotypes at diagnosis compared with those with late-onset T2DM. In particular, they tend to be more obese and have worse glycemic profiles, which is predicted to make the disease worse in the future, considering that the FPG level and BMI are important predictors of morbidity and mortality [ 47 ].…”
Section: Yod Among People With New-onset T2dm In South Koreamentioning
confidence: 99%
“…An increased risk of cardiovascular events has been reported in older patients with diabetes and particularly high comorbidities among those with low FBG levels (<95 mg/dL) [ 18 ]. In the general Korean population, the HR of all-cause mortality was significantly higher in the low (<70 mg/dL) and high FBG ranges (≥126 mg/dL) than in the reference range (80 to 99 mg/dL) [ 19 ]. In our study, we also a J-shaped association between FBG levels and all-cause mortality, as the range of 90 to 99 mg/dL was associated with the lowest risk of all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we also a J-shaped association between FBG levels and all-cause mortality, as the range of 90 to 99 mg/dL was associated with the lowest risk of all-cause mortality. The exact mechanism underlying the relationship between low FBG levels and a high risk of mortality remains unclear, although one possibility is that low FBG levels could indicate poor nutritional status, liver dysfunction, or other undetectable illnesses [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension was defined as diagnostic ICD‐10 codes (I10‐13 or I15) and at least one claim per year for antihypertensive medications. Dyslipidemia was defined as a diagnostic code (E78) and at least one claim per year for a lipid‐lowering agent 2 , 9 .…”
Section: Methodsmentioning
confidence: 99%